FORMS OF PROPERTY IN ROMAN LAW - Elena ANGHEL (Challenges of the Knowledge Society)
The exceptional vitality of the Roman legal system is explained both by the creation of the legal alphabet, taken over in later societies, and also by the fact that any society that was founded on private property and the exchange economy found all the concepts, principles and the legal institutions necessary to regulate these social relations. Thus, the legal institution of property is included among the concepts that make the connection between the past and the present of the rules of law. The appearance of the Roman state is placed in the 6th century BC, when King Servius Tullius institutes a series of reforms that ensure the transition from gentile society to the one organized in the state: social reform and administrative reform. In the pre-state era, legal texts attest to the existence of the collective property of land, as well as family property. With the emergence of the state, the Romans exercised collective property of the state as well as private property, called quiritary property, the Quirites being the ancient citizens of Rome. In the classical era, alongside the quiritary property, which survives the old era of Roman law, new forms of property appear: praetorian property, provincial property and peregrine property. In post-classical law, we witness a process of unification of property, perfected in the time of Emperor Justinian, a process that results in the merging of all forms of property into a single form, called dominium.